Neural correlates of emotional processing in panic disorder - Mayuresh S. Korgaonkar (Elsevier, 2021)
Background: Deficits in emotional processing are conceptualized in prevailing models of anxiety to underpin key symptoms of panic disorder (PD). Neuroimaging studies show evidence of aberrant neural functioning in PD patients during emotional processing, however little is understood about how non-conscious emotional processing impacts neural processes. Method: We examined activation and functional connectivity differences in brain regions involved in emotional processing between PD and healthy controls (HC) during subliminal and supraliminal presentations of facial emotions. Twenty-two PD and 33 HC participants were shown happy, sad, neutral, fear, anger and disgust facial expressions during functional magnetic resonance imaging using a 3T MRI scanner. We performed voxelwise ROI analyses at FWE-corrected p < 0.05 for main effects of group and group*emotion interactions. Results: There was less pregenual anterior cingulate cortex (pgACC) activation to subliminal presentations of happy and sad faces in PD compared to HC participants (group*emotion). In addition, PD patients had less pgACC - right amygdala connectivity than HC participants during sad and fear subliminal processing (group*emotion). PD patients also exhibited lower right cerebellum activity across all supraliminal presentations of facial expressions compared to HC. Conclusion: These findings suggest that there is aberrant neural processing in PD patients during both conscious and preconscious processing of both positive and negative stimuli, suggesting impaired recruitment of implicit regulatory networks during affective processing. It appears that PD patients may experience deficits in key regulatory connections between inhibitory and emotional neural networks at very early stages of processing of negative affective states.